Diagnostic yield of nontuberculous mycobacteria in patients booked for endoscopy at the University Teaching Hospital, Lusaka. (December 2017) - Chongwe, Gershom; Michelo, Charles; Kelly, Paul
Abstract Background The intestinal carriage of nontuberculous mycobacteria (NTM) is associated with disease, especially in severely immunocompromised individuals. These organisms, although often considered contaminants, have been known to cause various types of illnesses. We aimed to determine the prevalence of and associated factors for NTM among patients booked for colonoscopy at the University Teaching Hospital (UTH) in Lusaka. Methods We randomly recruited 97 patients attending routine endoscopy procedures between November 2012 and October 2013 and after consent, administered a structured questionnaire. We collected stool and intestinal lavage samples, as well as biopsy samples from the descending colon and the caecal area during the endoscopy procedure. Samples were cultured using the mycobacteria growth indicator tube (MGIT) method followed by the GenoType Mycobacterium CM/AS assay for identification of NTM. Results were expressed as means and standard deviations; proportions were expressed as percentages with corresponding 95% confidence intervals. We used Fisher's exact Chi square test for cross-tabulations where appropriate. All statistical tests were two-sided, with a significance level set at p < 0.05. Results Out of the 97 patients, 45 (46.4%) were female and 52 (53.6%) were males with mean ages 49.1 (±16.7, range 24–85) and 44.4 (±15.0, range 18–80) years respectively. The prevalence of NTM was 7.2% (95% CI 1.9–12.4), while that ofMycobacterium tuberculosis (MTB) was 6.2% (95% CI 2.3–13.0). Carriage of NTM was not significantly associated with age, sex or presenting symptoms such as diarrhoea, abdominal pain, weight loss as well as HIV status. There were no identifiable predictors of NTM carriage. Conclusion The results have shown that NTM and MTB are present in the intestines of the patients booked for colonoscopy at the University Teaching Hospital in Lusaka, but their presence is not related to presenting symptoms. Given that this may be an indicator of a bigger burden of NTM in this population, there is a need to explore this burden and the contribution it could have on abdominal disease in general as well as examine potential factors that might be important predictors.